(3GdMeGjI GdLfGFjI ddWad ef GdESJZdGd GdEbJUGOi (B: s (3OQGSI ebGQfI (B/ s - (3CHhHcQ CeMeO CMeO CMJjhTs; (3TQja SjO cGed s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3gPg GdQSGdI jOQS ef NdGdgG GdHGMK ehVhY GdMeGjI GdLfGFjI ddWad ef GdGSJZdGd GdGbJUGOi HCTcGdg GdeNJdaI(B: (3h HMK GdSjGSI GdJTQjYjI ai TbgG GdehVhYi(B: (3h GdJi JHfGgG SGHkbG abgGA GdTQjYI GdESdGejI(B: (3Ke HYO Pdc dGbJ GgJeGe GdeTpqQY GdhWfi h GdOhdi Ydi MO ShGA(B: (3h Pdc HZjI ehGLgI gPG GdfhY ef GdGSJZdGd(B: (3h GdPi CVMi ef GdLQGFe GdefXeI YHQ GdhWfjI(B: (3h eG jTcdg Pdc ef NWhQI HGYJHGQg jgOO CVYa GdaFGJ GdGLJeGYjI h gi aFI GdCWaGd(B: (3GdMeGjI GdLfGFjI ddWad ef GdGSJZdGd GdGbJUGOi ai GdehGKjb GdOhdjI(B: (3h GdMeGjI GdLfGFjI ddWad ef GdGSJZdGd GdGbJUGOi ai GdJTQjYGJ GdhWfjI(B: (3h bO dGMX GdHGMK Yeb GdXGgQI h JgOjOgG GdhGSY(B: (3dPdc HGJ gfGdc JMQc hGVM h edehS Ydi GdeSJhjjf GdOhdi h GdhWfi(B: (3QZe eMOhOjI Pdc h YOe JfGSHg eY MLe GdXGgQIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3HHdjhLQGajG(B: (3UaMGJ (B672-716s
Keywords: (3GdbGfhf GdLfGFj GdebGQfs; (3ehGLgI GdJLfjO GdbSQj ddCWaGds; (3GdMeGjI GdLfGFjI ddWad ef GdGSJZdGd GdGbJUGOj aj GdJTQjY GdOGNdis; (3GdMeGjI GdLfGFjI ddWad ef GdGSJZdGd GdGbJUGOj aj GdehGKjb GdOhdjIs; (3GdMeGjI GdehVhYjI ddWad ef GdGSJZdGd GdGbJUGOj aj GdehGKjb GdOhdjIs; (3MeGjI GdWad GdYGed aj GdTQjYI GdGSdGejI ef GdGSJZdGd GdGbJUGOis; (3MeGjI GdWad ef GdGSJZdGd GdGbJUGOj aj Gdegf GdGSJKfGFjI s; (3MeGjI GdWad ef GdGSJZdGd GdGbJUGOj aj GdNOeGJ GdeGdjIs; (3MeGjI GdWad ef GdGSJZdGd GdGbJUGOj aj GdGYeGd ZjQ GdeTQhYIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs